Chemically reactive transport of magnetized hybrid nanofluids through Darcian porous medium. (December 2021) - Waqas, Hassan; Farooq, Umar; Bukhari, Faisal Fareed; Alghamdi, Metib; Muhammad, Taseer
Abstract: Nowadays, nanofluid is the traditional procedure to increase the thermal conductivity of common fluids such as water, glycerin, and motor oil due to the deterioration of thermal aspects. The term "nanoliquid" refers to a liquid created by nanometer-sized particles with diameters less than 100 nm. Nanofluids are utilized in a variety of automotive purposes including fuel combustion, medication delivery, cooling of automobile engines, geothermal force extraction and heat transmission. This research aims to show the MHD transport of hybrid nanofluids with viscous dissipation through porous medium. By using an efficient similarity transformation process, PDEs are converted into system of nonlinear ODEs. The bvp4c (shooting method) is used to solve the complete nonlinear ODEs with suitable boundary conditions. To investigate the thermal transport aspects, hybrid nanoparticles and water as base fluid are used. To determine the flow behavior, several physical flow factors on velocity and thermal profiles are explored by using tables and graphs. The outcomes specify that porosity number and magnetic and slip parameters reduced the velocity profile. The higher estimations of slip parameter and Eckert number lead to stronger thermal profile. The concentration profile is decayed for growing estimations of chemical-reaction number.